Identifikasi Perbedaan Karakteristik Mutan (M3) Padi Inpago Unram 1 dan Mutan (M3) Padi Baas Selem - Suliartini, Ni Wayan Sri; Alfionita, Usi; Ujianto, Lestari; Aryana, I Gusti Putu Muliarta; Sudharmawan, Anak Agung Ketut (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
This research aims to determine the comparison of the characteristics of the mutant (M3) of Inpago Unram 1 rice with the mutant (M3) of Baas Selem rice and the comparison of the characteristics of the mutant line (M3) with its parents.  The research was carried out from March to November 2022 in Saribaye Village, Lingsar District, West Lombok.  The method used is an experimental method in the field.  The experiment was carried out using a Randomized Block Design (RAK) with 8 genotypes and repeated 3 times.  Blocks were planted as many as 20 plants and then 4 sample plants were taken.  The data were analyzed using a significance level of 5%, then further tested using an orthogonal contrast test of 5% significance level.  The results of the research showed significant differences in the characteristics of the number of productive tillers, total number of tillers, panicle length, number of filled grains per panicle, weight of 100 grains and weight of filled grains per hill, then further tests showed 6 significantly different characters in the comparison of G1, G2, G3,  G4 >< G5, G6, G7, G8 (Inpago Unram 1 lines compared to Baas Selem lines).  In the comparison of G1 >< G2, G3, G4 (Inpago Unram 1 parent compared with its lines) showed significantly different results regarding the panicle length character.  The comparison of G5 >< G6, G7, G8 (Baas Selem parents compared with their lines) showed significantly different results regarding the character of the number of productive offspring and the total number of offspring.